Analisis Komparatif Mekanisme Verifikasi Investor Asing dan Penjamin dalam Perspektif Intelijen Keimigrasian di Indonesia, Belanda, dan Singapura - Kresna Riyadi Rum; Maulana Budi Putra; Geraldo Agmar Hamid (Universitas Medan Area, 2026)
This study aims to analyze and compare foreign investor and guarantor verification mechanisms from the perspective of immigration intelligence in Indonesia, the Netherlands, and Singapore. The research method used is normative legal research with a comparative legal approach, through an analysis of laws and regulations, immigration policies, and relevant literature from the three countries. The results show that Indonesia still places foreign investor and guarantor verification primarily on administrative aspects and document compliance, even though immigration intelligence functions have begun to be integrated into the oversight process. In contrast, the Netherlands implements a risk-based verification mechanism that involves inter-agency data exchange and a comprehensive assessment of investor backgrounds. Singapore has developed a digitally integrated verification system supported by data analysis and strict oversight of funding sources, business track records, and sponsors or guarantors involved. This comparison demonstrates that the effectiveness of foreign investor verification depends not only on completing administrative requirements but also on optimizing immigration intelligence functions through the use of information technology, data integration, and inter-agency cooperation. This study recommends strengthening immigration intelligence mechanisms in Indonesia through the development of a risk-based verification system and increased inter-agency coordination to support national security and increase investment competitiveness.